Thickness‐Driven Morphotropic Phase Transition in Metastable Ferroelectric CaTiO3 Films. (28th March 2022) - Lee, Ji Hye; Kim, Hong Joon; Ryoo, Eunjo; Jang, Jinhyuk; Kim, Sanghyeon; Kim, Jeong Rae; Park, Se Young; Choi, Si‐Young; Noh, Tae Won; Lee, Daesu
Abstract: The intimate coexistence of multiple phases in ferroelectrics has been shown to result in exotic electromechanical properties, such as giant piezoelectricity. Here, via a thickness‐driven phase transition, the phase coexistence and enhanced piezoelectricity in a few tens of nanometers thick, Pb‐free CaTiO3 films are demonstrated. Due to the competition between interfacial and bulk energies, as film thickness increases, epitaxial CaTiO3 films exhibit a ferroelectric‐to‐paraelectric phase transition that is concomitant with the rhombohedral‐to‐orthorhombic structural transition. This so‐called thickness‐driven morphotropic phase transition (MPT) in nanoscale CaTiO3 films stems from the metastable nature of ferroelectricity. The resulting morphotropic phase boundary at the atomic scale in nanoscale CaTiO3 films is visualized. It is also shown that this thickness‐driven MPT can lead to reasonably good piezoelectricity at the nanoscale. This study highlights the rich phase evolution of complex ferroelectrics as a novel platform to control the functionality of nanoscale electromechanical devices. Abstract : A new strategy to enhance nanoelectromechanical properties in Pb‐free CaTiO3 based on the film thickness‐driven morphotropic phase transition and associated formation of morphotropic phase boundaries is demonstrated. The morphotropic phase boundary in nanoscale CaTiO3 films, stemming from metastable ferroelectricity, leads to good piezoelectricity at the nanoscale.